KOLABORASI ORANG TUA DAN GURU DALAM MENDUKUNG PERKEMBANGAN KEMAMPUAN BERPIKIR KRITIS ANAK - Suparmi; Hardaningtyas, Khoirunisa; Mah'ruf Todi Prihantoro (Al-ATHFAL: Jurnal Pendidikan Anak, 2024)
Indonesia's 21st century education system emphasizes the importance of critical thinking skills in the development of every child. Collaboration between parents and teachers is a method that can be used to support the development of children's critical thinking skills. Effective communication can encourage cooperation in creating an interactive and supportive learning environment, both at home and at school, so that children can learn the thinking skills needed to face the challenges of the modern world. This article aims to find out (1) how collaboration between parents and teachers can effectively improve children's critical thinking skills, (2) the obstacles that are often faced in collaborative efforts between parents and teachers to improve children's critical thinking skills and solutions to the obstacles experienced. This article uses the literature review method by obtaining 100 sources from articles, books, and repositories, then the data is analyzed and gets 10 main articles. The results show that collaboration between parents and teachers creates a consistent learning environment, both at home and at school. In conclusion, the role of parents and teachers is very important in children's learning process, especially in developing critical thinking skills that are the foundation for their future. Keywords:  Parents; Teachers; Critical Thinking; Children